All Roads Lead to Rome?: Decadence, Paganism, Catholicism and the Later Life of Oscar Wilde - Shushma Malik (Cahiers Victoriens et Edouardiens)
This article examines paganism, Catholicism and decadence in the life and letters of the writer and wit Oscar Wilde, focusing in particular on the period after his release from Reading Gaol. In his travels through France and Italy between 1897 and 1900, Wilde labels the behaviour that led to his imprisonment as belonging to his decadent ‘pagan days’ and ‘Neronian hours’. As the writer struggles to reconcile his past paganism with his present, renewed, Catholicism, he goes back and forth between the two, and only at Rome can Wilde find his solution. In a city that exhibits both its paganism and Catholicism to its visitors, Wilde can finally indulge all aspects of his ‘Romanness’ in one place at the same time.